Uji Aktivitas Antelmintik Ekstrak Etanol Kulit Buah Petai Cina (Leucaena leucocephala (Lam.) de Wit) terhadap Ascaris suum Goeze secara In Vitro - Najwa Khalisha Putri; Siti Hazar; Umi Yuniarni (Bandung Conference Series: Pharmacy, 2024)
Abstract. Helminthiasis is an infection caused by parasitic intestinal worms from the intestinal nematoda group that can be transmitted through soil. This infection is also known as Soil Transmitted Helminths (STH). One of the plants that can be used as an alternative treatment for worm infections is the peel of Chinese petai fruit (Leucaena leucocephala (Lam.) de Wit). This study aims to investigate and evaluate the effects of ethanol extract from the peel of Chinese petai fruit (Leucaena leucocephala (Lam.) de Wit) as an anthelmintic against Ascaris suum Goeze in vitro. Testing was conducted on male and female pig roundworms as well as worm eggs. The subjects were divided into five test groups: the control group was given 0.9% NaCl, the test groups were given ethanol extract of Chinese petai fruit peel at concentrations of 1.25%, 2.5%, and 5%, the comparison group for worms was given 0.2% pyrantel pamoate, and for eggs, 0.12% albendazole. The parameters for observing anthelmintic activity in adult pig roundworms were paralysis and death of the worms, while the parameters for observing anthelmintic activity in worm eggs were the number of fertile eggs and the percentage of inhibition. The results of the tests on adult worms and worm eggs showed that 5% ethanol extract of Chinese petai fruit peel had the strongest anthelmintic activity with a spastic paralysis type and had an inhibition percentage of 73,3% on worm eggs. Abstrak. Kecacingan adalah suatu infeksi yang disebabkan oleh cacing parasit usus dari kelompok nematoda usus yang dapat ditularkan melalui tanah. Infeksi ini juga dikenal sebagai Soil Transmitted Helminths (STH). Salah satu tanaman yang dapat dijadikan sebagai pengobatan alternatif infeksi cacing, yaitu kulit buah petai cina (Leucaena leucocephala (Lam.) de Wit. Penelitian ini bertujuan untuk mengetahui dan menilai efek ekstrak etanol kulit buah petai cina (Leucaena leucocephala (Lam.) de Wit) sebagai antelmintik terhadap Ascaris suum Goeze secara in vitro. Pengujian dilakukan terhadap cacing gelang babi jantan dan betina juga telur cacing. Yang dibagi kedalam lima kelompok uji yaitu kelompok kontrol diberi NaCl 0,9%, kelompok uji diberi sediaan ekstrak etanol kulit buah petai cina dengan konsentrasi 1,25%, 2,5%, 5%, kelompok pembanding untuk cacing diberi pirantel pamoat 0,2% dan untuk telur diberi albendazol 0,12%. Parameter pengamatan uji aktivitas antelmintik pada cacing gelang babi dewasa yaitu paralisis dan kematian pada cacing, sedangkan parameter pengamatan uji aktivitas antelmintik pada telur cacing itu jumlah telur fertil dan (%) inhibisi. Hasil pengujian pada cacing dewasa dan telur cacing menunjukkan bahwa ekstrak etanol kulit buah petai cina 5% memiliki aktivitas antelmintik paling kuat dengan tipe paralisis spastik untuk cacing, serta memiliki persen inhibisi 73,3% pada telur cacing.